Exploiting liars' verbal strategies by examining the verifiability of details - Nahari, Galit (Legal and criminological psychology, 2014)
Background We examined the hypothesis that liars will report their activities strategically and will, if possible, avoid mentioning details that can be verified by the investigator. Method A total of 38 participants wrote a statement in which they told the truth or lied about their activities during a recent 30-minute period. Two coders counted the frequency of occurrence of details that can be verified and that cannot be verified. Results Liars, compared with truth tellers, included fewer details that can be verified and an equal number of details that cannot be verified in their statement, and the ratio between verifiable and unverifiable details was smaller in liars compared with truth tellers. High percentages of truth tellers and liars were classified correctly based on the frequency counting of verifiable details (79%) or the ratio between verifiable and unverifiable details (71%). Those percentages were higher than the percentage that could be classified correctly (63%) based on verifiable and unverifiable detail combined. We compared our verifiability approach with other theoretical approaches as to why differences in detail between truth tellers and liars emerge.